Peningkatan Kualitas Layanan Administrasi Pendidikan Melalui Optimalisasi Pengelolaan Tata Usaha - Zahiq, Moh; Mustofa, Ali; Fatachul Aziz, Ahmad; Maskhuroh, Lailatul (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article aims to describe the improvement of school administrative service quality through the optimisation of administrative management at SMK Baitussalam Bluluk Lamongan. This is a qualitative study. The informants in this study were the principal, vice principal for curriculum, teachers, students, and administrative staff. Data collection was conducted using observation, interviews, and documentation techniques. Data analysis was conducted through data reduction, data presentation, and conclusions. Furthermore, the data validity was tested through triangulation, conducting more thorough observations and interviews. The results of this study indicate that the implementation of administration in improving the quality of administrative services at SMK Baitussalam Bluluk Lamongan has been carried out in accordance with the predetermined plan. The performance of administrative staff in implementing administration to improve the quality of administrative services at SMK Baitussalam Bluluk Lamongan is in accordance with their respective duties and functions. Then, the optimisation of administrative management at SMK Baitussalam Bluluk Lamongan has a function, namely POAC (planning, organising, actuating, controlling). The existence of a management function serves as a benchmark that good management must be in accordance with the existing stages. Planning is the first point in the management function.